Mitigating Dietary Microplastic Accumulation and Oxidative Stress Response in European Seabass (Dicentrarchus labrax) Juveniles Using a Natural Microencapsulated Antioxidant - Matteo Zarantoniello; Nico Cattaneo; Federico Conti; Margherita Carrino; Gloriana Cardinaletti; İdris Şener; Ike Olivotto (MDPI AG, 2024)
Aquafeed's contamination by microplastics can pose a risk to fish health and quality since they can be absorbed by the gastrointestinal tract and translocate to different tissues. The liver acts as a retaining organ with the consequent triggering of oxidative stress response. The present study aimed to combine the use of natural astaxanthin with natural-based microcapsules to counteract these negative side effects. European seabass juveniles were fed diets containing commercially available fluorescent microplastic microbeads (1-5 μm; 50 mg/kg feed) alone or combined with microencapsulated astaxanthin (AX) (7 g/kg feed; tested for half or whole feeding trial-30 or 60 days, respectively). Fish from the different dietary treatments did not evidence variations in survival and growth performance and did not show pathological alterations at the intestinal level. However, the microplastics were absorbed at the intestinal level with a consequent translocation to the liver, leading, when provided solely, to sod1, sod2, and cat upregulation. Interestingly, the dietary implementation of microencapsulated AX led to a mitigation of oxidative stress. In addition, the microcapsules, due to their composition, promoted microplastic coagulation in the fish gut, limiting their absorption and accumulation in all the tissues analyzed. These results were supported by in vitro tests, which demonstrated that the microcapsules promoted microplastic coagula formation too large to be absorbed at the intestinal level and by the fact that the coagulated microplastics were released through the fish feces.